PENINGKATAN PRODUKTIVITAS DAN EFISIENSI PENEBANGAN KAYU MANGIUM DI SATU PERUSAHAAN HUTAN TANAMAN DI PROPINSI JAMBI - Sona Suhartana; Marolop Sinaga; Ishak Sumantri (Jurnal Penelitian Hasil Hutan, 2004)
Implementation  of  felling  technique in the timber  estate is not  yet practiced  efficiently and appropriately.  Study  on  the lowest possible felling  technique  (LPFT) is considered  important to increase fellingproductivity and felling  efficiency. This study was carried out at a timber estate  in iambi  in 2003. The aim of this study was to determine the effectof LPFT on fellingproductivity and efficiency.Data collected in this regard were: working time,  wood volume, productivity,  efficiency, stump height and felling  cost.  Two-categories data were analyzed with respect to their possible differences using a t-test.Results revealed that implementation of LPFT brought out more convenient impacts in comparison  to  the  conventional felling   technique  (CFT),   as follows:   (1)   Felling  productivity increased  at  3.177  m3/hr;  (2) felling efficiency  increased  approximately  7.4%;  (3) felling cost decreased by some Rp 159.1;   and (4) the average stump height were 21.14  cm for LPFT  and 32.83 cmforCFT